Commercially Available Gene Expression Assays as Predictive Tools for Adjuvant Radiotherapy? A Critical Review - Krug, David; Baumann, René; Budach, Wilfried; Duma, Marciana Nona; Dunst, Jürgen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Hehr, Thomas; Piroth, Marc D.; Sedlmayer, Felix; et al. (Breast Care, 2020)
Background: Gene expression assays are increasingly used for decision-making regarding adjuvant chemotherapy in patients with hormone receptor-positive, HER2-negative breast cancer. There are some clinical situations in which there is also a need for better prognostic and predictive markers to better estimate the amount of benefit from adjuvant radiotherapy. The rising availability of gene expression analyses prompts the question whether their results can also be used to guide clinical decisions regarding adjuvant radiation. Summary: Multiple studies suggest a correlation between results from gene expression assays and locoregional recurrence rates. Only few publications addressed the predictive value of results from gene expression analysis for the role of adjuvant radiotherapy in different settings. Key Messages: To date, the available evidence on the possible predictive value of gene expression assays for radiotherapy does not support their inclusion into the decision-making process for adjuvant radiation. This is due to methodological weaknesses and limitations regarding patient selection, the nonrandomized design of all studies in terms of radiotherapy use, and limited availability of tissue from prospective trials. Thus, utilization of the present knowledge for clinical indication of radiotherapy should be very cautious.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Breast cancer; Gene expression assay; Oncotype DX; Predictive marker; Radiotherapy